2001
DOI: 10.1002/1521-4141(200106)31:6<1917::aid-immu1917>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the origin of CD44high "memory phenotype" CD8 T cells: comparison between memory CD8 T cells and thymus-independent CD8 T cells

Abstract: CD44highCD8 T cells in naive mice, which increase with age, and are often referred to as memory CD8 T cells. However, since thymus‐independent CD8 T cells have also been shown to be CD44high, the origin of the CD44highCD8 T cells in naive mice remains unclear. In this study, we compared the characteristics of memory CD8 T cells and thymus‐independent CD8 T cells in TCR transgenic mice to clarify the origin of the CD44highCD8 T cells in naive normal mice. The memory and thymus‐independent CD8 T cells showed dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…In agreement with a previous study, 8 we found that the CD8 lo cells proliferated poorly to antigen stimulation in the absence of IL-2 ( Figure 2A, upper panel). The CD8 int cells also showed a similar proliferative defect.…”
Section: Cd8 T Cells From Male H-y Mice Possess An Increased Activatisupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous study, 8 we found that the CD8 lo cells proliferated poorly to antigen stimulation in the absence of IL-2 ( Figure 2A, upper panel). The CD8 int cells also showed a similar proliferative defect.…”
Section: Cd8 T Cells From Male H-y Mice Possess An Increased Activatisupporting
confidence: 93%
“…However, they differ from conventional memory T cells in that they are more refractory to activation by antigen compared with naive T cells. 7,8 von Boehmer et al 5 have shown that the development of CD8 lo cells is thymus dependent, since the cells are not found in male H-2 b H-Y nude mice. By contrast, Yamada et al 6 found that CD8 lo cells developed normally in thymectomized male but not female H-2 b mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these cells also proliferate weakly in response to anti-CD3 plus anti-CD28 stimulation (data not shown). In this respect they are similar to memory phenotype CD8 T cells, which are generated following homeostatic proliferation in other TCR-transgenic systems (6) and to thymus-independent T cells (33). This last point highlights the fact that CD44 high CD122 ϩ CD8 T cells in F5 but also in wild-type mice, where they are classically identified as memory cells, could be heterogeneous not only in their antigenic specificity but also in their generation requirements.…”
Section: Discussionmentioning
confidence: 64%
“…However, during homeostatic or lymphopenia-induced proliferation, naive CD8 T cells can also acquire a memory phenotype, as shown by up-regulation of CD44 and KLRG1, and by their ability to secrete cytokines (47)(48)(49)(50). CD44 high memory phenotype CD8 T cells in normal naive mice have also been shown to exhibit characteristics similar to thymus-independent CD8 T cells (51). Thus, many memory phenotype CD8 T cells may not be true Agexperienced memory cells.…”
Section: Discussionmentioning
confidence: 99%